ANALISIS SUB SEKTOR PERKEBUNAN KABUPATEN MUARO JAMBI - Suri, Putri Intan; Achmad, Erni; Aminah, Siti (e-Journal Perdagangan Industri dan Moneter, 2017)
The purpose of this study are: (1) to determine and analyze the progress of labor, land area, total production, and the type of plantation commodities period of 2001-2013. (2) to determine and analyze the contribution of plantation sub-sector of the agricultural sector and GDP (Gross Domestic Product) Muaro Jambi period of 2001-2013. (3) to determine and analyze the role of plantation sub-sector to the economy in Muaro Jambi period of 2001-2013. This study used secondary data obtained from Statistics of Muaro Jambi and Dinas Perkebunan of Muaro Jambi. The descriptive analysis method qualitative and quantitative descriptive. To view the role of plantation sub-sector to the economy of the area using the model Location Quotient (LQ). The development of plantation sub-sector workforce Muaro Jambi period of 2001-2013 fluctuated. The average number of workers in the plantation sub-sector in Muaro Jambi is 5.05%. Type of plantation crops derived from people's plantations such as rubber, oil palm, coconut, hybrid coconut, robusta coffee, pepper, cocoa, nut, hazelnut, cardamom, cotton, palm. While large plantations state and private estates include rubber and palm oil. The development of the land area of plantation sub-sector in Muaro Jambi during the period of 2001-2013 amounted to 3.53% on average per year. Plantation sub-sector GDP contribution in Muaro Jambi period of 2001-2013 amounted to 50.97%. The role of plantation sub-sector Muaro Jambi 2001-2013 period average of 1.3037 is the base (LQ> 1).